2007
DOI: 10.1152/ajpregu.00821.2006
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of synchronized gastric electrical stimulation for gastroparesis: enhanced gastric motility in dogs

Abstract: The aim of this study was to determine the effects and mechanism of synchronized gastric electrical stimulation (SGES) on gastric contractions and gastric emptying. The first experiment was designed to study the effects of SGES on antral contractions in four randomized sessions. Sessions 1 (control) and 2 (atropine) were performed in the fasting state, composed of three 30-min periods (baseline, stimulation, and recovery). Sessions 3 (control) and 4 (SGES performed during 2nd 20-min period) were performed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…The excitatory effect of synchronized IES was blocked by atropine [49]. Similarly, gastric contractions were improved with synchronized gastric electrical stimulation [62] and sequential multi-channel gastric electrical stimulation [63,64]. The excitatory effect of synchronized IES on intestinal contraction is of clinical importance and may be used to treat patients with intestinal hypomotility that is commonly seen in patients with chronic intestinal pseudoobstruction or postoperative ileus.…”
Section: Effects and Mechanisms Of Ies On Intestinal Motilitymentioning
confidence: 99%
“…The excitatory effect of synchronized IES was blocked by atropine [49]. Similarly, gastric contractions were improved with synchronized gastric electrical stimulation [62] and sequential multi-channel gastric electrical stimulation [63,64]. The excitatory effect of synchronized IES on intestinal contraction is of clinical importance and may be used to treat patients with intestinal hypomotility that is commonly seen in patients with chronic intestinal pseudoobstruction or postoperative ileus.…”
Section: Effects and Mechanisms Of Ies On Intestinal Motilitymentioning
confidence: 99%
“…A novel method has recently been proposed: synchronized GES. 98 Synchronized GES requires the implantation of two pairs of electrodes, one for the detection of gastric slow waves and the other for stimulation. In this proposed method, each electrical stimulus was delivered upon the detection of an intrinsic slow wave peak, i.e.…”
Section: Synchronized Gesmentioning
confidence: 99%
“…A recent canine study showed that synchronized GES in fasting state significantly increased the amplitude of gastric contractions and improved the impaired postprandial antral motility induced by glucagons. 98 Apparently, this method can only be applied in patients with normal gastric slow waves but antral hypomotility. It would fail if gastric slow waves were dysrhythmic.…”
Section: Synchronized Gesmentioning
confidence: 99%
“…Dual-pulse GES, combined with both short pulses and long pulses, has advantages of both long-pulse GES and short-pulse GES and is capable of improving dysrhythmia and nausea and vomiting (48). Recently, a number of studies have shown that synchronized GES (or SGES, electrical stimuli are delivered at the occurrence of intrinsic slow waves) has a prokinetic effect: increasing antral contractions and accelerating gastric empty (47,57,59). However, it is unknown whether SGES is able to improve or impair (similar to prokinetics) gastric accommodation, and this is crucial if SGES is to be used for treating gastroparesis and functional dyspepsia, since impaired accommodation is common in these diseases.…”
mentioning
confidence: 99%